PRODUCTIVITY MEASUREMENT IN PT. SELAMAT PRAMA ARTA USING TOTAL FACTOR PRODUCTIVITY METHOD - LINGGADJAJA (NIM : 29108024); Pembimbing: Dr. Ir. Mursyid Hasan Basri, EKA
Productivity is one of the important measures in industry since it describes how well a company utilizes its resources to produce a certain output. One method to measure productivity in industries is called total factor productivity. In this research, productivity in PT. Selamat Prama Arta, which is a tea sortation company was calculated by using total factor productivity method. The productivity was calculated for six financial periods from 2003 to 2008. First, a study to calculate productivity using total factor productivity method was conducted. Then, research was by collecting datas that are required for the calculation and then company's productivity was calculated using total factor productivity, which is proposed by Mizobuchi. After that, analysis was continued by evaluating other factors that affect company's productivity by using multiple linier regression analysis. Then, factors which were found using the multiple linier regression analysis were statistically analyzed to evaluated significance level of each factor to company's productivity. The results showed that the most affecting factor to the company's productivity is added value. Added value itself composed by two components which are sales and cost of goods sold. Solutions that proposed to the company to increase its productivity include : increase production capacity by creating a new production plant, record all customer's demand and conducting a demand forecast, and conducting a warehouse checking and maintenance periodically.